1988
DOI: 10.1136/thx.43.7.552
|View full text |Cite
|
Sign up to set email alerts
|

Effect of histamine on proliferation of normal human adult lung fibroblasts.

Abstract: Fibrotic lung tissue shows increased connective tissue deposition and fibroblast proliferation and in addition a substantial increase in mast cell numbers in and around the fibrotic area. To elucidate the question ofwhether products of mast cells affect the proliferative behaviour of structural cells in the lung and thereby contribute to fibrogenesis, the effect of histamine, a prominent mast cell derived mediator, on the in vitro proliferation of primary cultures of normal adult human lung fibroblasts was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
66
1
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 23 publications
3
66
1
2
Order By: Relevance
“…Primary Cell Culture-Primary human lung fibroblasts (phLF) were isolated from organ donor lungs and cultured as previously described (37)(38)(39). 24 h prior to treatment phLF were synchronized by incubation in starvation medium containing 1% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Primary Cell Culture-Primary human lung fibroblasts (phLF) were isolated from organ donor lungs and cultured as previously described (37)(38)(39). 24 h prior to treatment phLF were synchronized by incubation in starvation medium containing 1% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Agents targeting the inflammatory macrophages, neutrophils, and lymphocytes have not halted pathologic fibrosis. The increased numbers of mast cells associated with pulmonary fibrosis is well documented, as they also contribute to the inflammatory response but their role is unclear (Kawanami et al, 1979;Jordana et al, 1988). Clinically, a correlation between mast cells and fibrosis is recognized, but a causal relationship linking mast cells and fibroblasts to fibrogenesis has yet to be demonstrated (Metcalfe et al, 1997).…”
mentioning
confidence: 99%
“…We previously reported that lung mast cells synthesize and release renin, which triggers local ANG II formation (Silver et al, 2004;Veerappan et al, 2008). Histamine, another mast cell mediator, may also contribute to fibrosis by stimulating fibroblast proliferation ( Jordana et al, 1988).…”
mentioning
confidence: 99%
“…MC promote migration and proliferation of fibroblasts by releasing proinflammatory mediators and growth factors (16,17). For example, MC tryptase is able to activate and induce proliferation of fibroblasts (18).…”
mentioning
confidence: 99%